1999
DOI: 10.1007/s11626-999-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

H-ras-transformed NRK-52E renal epithelial cells have altered growth, morphology, and cytoskeletal structure that correlates with renal cell carcinoma in vivo

Abstract: We studied the effect of the ras oncogene on the growth kinetics, morphology, cytoskeletal structure, and tumorigenicity of the widely used NRK-52E rat kidney epithelial cell line and two H-ras oncogene-transformed cell lines, H/1.2-NRK-52E (H/1.2) and H/6.1-NRK-52E (H/6.1). Population doubling times of NRK-52E, H/1.2, and H/6.1 cells were 28, 26, and 24 h, respectively, with the transformed cells reaching higher saturation densities than the parent cells. NRK-52E cells had typical epithelial morphology with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…RCCs are extremely resistant to conventional cancer therapies, and no effective systemic therapy presently exists for patients with metastatic RCCs. Although some apoptosis-related genes have altered expression in RCCs, this appears to relate largely to genes that have functions in the broader context of apoptosis induction, such as H-Ras [29], rather than genes whose products make up the apoptosis pathway itself, for example, the Bcl-2-gene family. Kolenko et al [22]have demonstrated in some human-derived RCC cell lines that caspase-3 expression is low or lacking.…”
Section: Discussionmentioning
confidence: 99%
“…RCCs are extremely resistant to conventional cancer therapies, and no effective systemic therapy presently exists for patients with metastatic RCCs. Although some apoptosis-related genes have altered expression in RCCs, this appears to relate largely to genes that have functions in the broader context of apoptosis induction, such as H-Ras [29], rather than genes whose products make up the apoptosis pathway itself, for example, the Bcl-2-gene family. Kolenko et al [22]have demonstrated in some human-derived RCC cell lines that caspase-3 expression is low or lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line, derived from the proximal tubule epithelium (PTE) of the rat kidney, is non-tumorigenic, and retains many morphological and physiological characteristics of PTE in vivo [18, 19]. Cells were incubated in Dulbecco’s modified Eagle’s medium (DMEM) with 10% fetal bovine serum and antibiotics (100 U/ml penicillin, 100 µg/ml streptomycin) at 37°C in 95% O 2 /5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…TSP-1 at 1 µg/ml was added to cultured kidney proximal tubule (NRK) cells and studied at 24 and 48 hours for evidence of apoptosis by cytochrome c release and caspase-3 activity. The NRK-52E normal kidney cell line is derived from the proximal tubule epithelium (PTE) of the rat kidney, is nontumorigenic, retains many morphological and physiological characteristics of PTE, and has been used to mimic changes in vivo (31)(32)(33). Cytochrome c apoptosis detection kit (Alexa Fluor 488 assay; Invitrogen Corp.) was used to perform the apoptosis assay.…”
Section: Kidney Ir Injury: Animal Model Kidney Ir Injury Was Inducedmentioning
confidence: 99%